La burocracia y su influencia en la ética profesional de las secretarias de transvial ep - Villagómez Bravo, Paola Victoria (2021)
This research addressed the issue of the influence of bureaucracy on the professional ethics of the secretaries of the TRASVIAL EP. Due to the fact that at present the ethics of some public servants has been tainted by dishonest events, therefore it was necessary to inquire about the bureaucracy, its complexity, rigidity and the effects that it may have on the ethics and the work performance of the secretaries . The main objective of the research is to determine how and why the bureaucracy can affect the professional ethics of the secretaries of TRANSVIAL EP in order to establish their ethical values ​​such as their professionalism and how strong the pressure from senior officials can be. executive axes to accept or reject the proposal to commit an unethical act; The technique that was used for data collection was a survey applied in person and individually to the secretaries of the institution within the offices of the same, through which we were able to know their different opinions regarding the questions raised. According to the analysis that was carried out, it was possible to conclude that the bureaucratic system needs to be restructured so that it reduces by a large percentage the complexity of some procedures for the satisfaction of the citizens and the agile performance of the secretaries, this will also help to break with the chain of dishonest acts, in which public institutions are especially involved on a daily basis